PERAN GURU DALAM PENCEGAHAN DAN PENANGANAN PERILAKU BULLYING PADA SISWA DI SEKOLAH DASAR (STUDI KASUS: SD 3 TERBAN) - Yusriyah, Naily; Ikhrom, Ikhrom; Aini, Dewi Khurun (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
Bullying behavior remains widespread today, even among children. Therefore, teachers play an important role in preventing and handling bullying. This study aims to describe the role of teachers in preventing and managing bullying at elementary school level. A qualitative approach was used through interviews, observations, and documentation involving the principal, classroom teachers, and parents at SD 3 Terban. The results show that teachers have performed their roles well despite the absence of a school counselor. The protocol requires students to report incidents to the classroom teacher, who then informs the principal, acting as a counselor. The school also collaborates with police, prosecutors, and other institutions to prevent bullying and uses advanced camera technology to monitor student honesty. The study suggests that teachers should continuously evaluate and improve their role to maximize bullying prevention and intervention at school.